Gender Differences in Insomnia and Role of Work Characteristics and Family Responsibilities Among Healthcare Workers in Taiwanese Tertiary Hospitals - Tsou, Meng-Ting (Frontiers in Psychiatry, 2022)
Background: Insomnia is common among healthcare workers (HCWs), especially those working in tertiary hospitals. This study aimed to clarify whether gender differences in insomnia could be explained by gender differences in work characteristics and family responsibilities among tertiary hospital HCWs in Taiwan. Methods: This cross-sectional study was conducted in 22 departments of two tertiary hospitals in Northern Taiwan from December 2018 to March 2019. All data were obtained by a self-administered questionnaire given when participants underwent annual health check-ups. Insomnia was evaluated using the Chinese Athens Insomnia Scale. Work characteristics and family responsibilities were as follows: department, working hours, shift work, visual display terminals used at work, demand-control-support model, burnout level, breadwinner status, living conditions, and caregiver status. Data of 2,811 participants (317 men, 11.3%; 2,494 women, 88.7%) were analyzed (response rate: men, 85%; women, 88%). Logistic regression analysis examined up to what extent work characteristics and family responsibilities explained gender differences in insomnia. Results: The prevalence of insomnia in women (61.7%) was significantly higher than that in men (52.7%), and gender differences strengthened after adjusting for work characteristics and family responsibilities (odds ratio: 1.45 and 1.62, p < 0.01). Stratified analyses revealed that significant gender differences were found among HCWs with comparatively unfavorable work and family conditions. Women were at a higher risk of insomnia owing to these factors. Conclusion: These results suggest that gender differences in insomnia among HCWs are mainly explained by gender differences in work characteristics and family